2020
DOI: 10.3390/ijerph17239151
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review on Air Quality Monitoring, Policy and Health in West African Cities

Abstract: Ambient air pollution is a global health threat that causes severe mortality and morbidity from respiratory, cardiovascular, and other diseases. Its impact is especially concerning in cities; as the urban population increases, especially in low- and middle-income countries, large populations risk suffering from these health effects. The Economic Community of West African States (ECOWAS) comprises 15 West African countries, in which many cities are currently experiencing fast growth and industrialization. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 39 publications
(114 reference statements)
0
27
0
Order By: Relevance
“…From the information that is available, there are numerous locations with raised pollution, particularly roadside locations [9]. Whilst some air quality monitoring exists in Nigeria [24][25][26] infrastructure is limited, and the problem of increasing urbanization and a lack of regulation of pollutant levels has resulted in extremely poor air quality [27].…”
Section: Introductionmentioning
confidence: 99%
“…From the information that is available, there are numerous locations with raised pollution, particularly roadside locations [9]. Whilst some air quality monitoring exists in Nigeria [24][25][26] infrastructure is limited, and the problem of increasing urbanization and a lack of regulation of pollutant levels has resulted in extremely poor air quality [27].…”
Section: Introductionmentioning
confidence: 99%
“…The regulation and governance of air pollution has proven to be an immense challenge in LICs and LMICs, particularly in Sub-Saharan Africa (Amegah and Agyei-Mensah, 2017;Makoni, 2020;Mir Alvarez et al, 2020). For instance, a study found that most African countries have not incorporated the World Health Organization's (WHO) air pollution guidelines into their national legislations, and 45% of African countries did not have any air pollution regulations whatsoever (Joss et al, 2017).…”
Section: Ambient Air Pollutionmentioning
confidence: 99%
“…Air pollution is a leading environmental-health challenge facing urban areas around the world today [ 3 , 21 ] since 55% of the world's population is urbanised [30] and 60% will be urbanised by 2030 [17] . Furthermore, on a global scale urban environments are estimated to contribute 75% of greenhouse gas emissions [17] .…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has also brought back the spotlight on air quality issues. There is overwhelming evidence that links air pollution and the proliferation of co-morbidities (for example cardiovascular disease, respiratory illnesses, heart disease, diabetes) and an increase in COVID-19 complicated related deaths [3] . The threat is heightened when an individual is exposed to high levels of air pollution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation